LEADERSHIP TRANSFORMATIONAL AND SERVANT LEADERSHIP: A THEORETICAL STUDY ON QUALITY MANAGEMENT IN ISLAMIC EDUCATION INSTITUTIONS - Salamah, Wichda Ainis; Sukarman (Indonesian Journal of Social Science and Education (IJOSSE), 2026)
This research aims to conduct a theoretical comparative analysis between Transformational Leadership and Servant Leadership models in the context of quality improvement in Islamic educational institutions. As a library research, this article synthesizes various contemporary management literatures and Islamic leadership treasures to find the most effective leadership model for educational institution development. The results show that transformational leadership is crucial in accelerating vision, innovation, and organizational culture change oriented towards quality (itqan). On the other hand, servant leadership provides a foundation for strengthening teamwork through a service-oriented approach (khidmah) and empathy, which is aligned with prophetic values. The conclusion of this study emphasizes that the synergy between transformational vision and a service-oriented spirit is the key to building a sustainable quality culture in Islamic educational institutions, where leaders are able to encourage organizational achievement while maintaining internal team harmony through the spirit of ukhuwah and ta’awun.